Análisis jurídico – doctrinario de las instituciones del matrimonio y la unión de hecho, como base fundamental de la sociedad. - Calero Freire, David Napoleón (2023)
The purpose of this work is to analyze the legal institution of marriage and common-law union. The foundation of a society is the nuclear family, which, since the beginning of society, has been formed by legally married nuclear families, constituting the legal institution of marriage. Additionally, there are those families who, without a legal document, contract, or formalization, have maintained a relationship for several years by choice. This type of relationship is recognized in Ecuadorian civil regulations as a common-law union, a legal institution that, under certain conditions, can have effects similar to those of civil marriage. Perform an analysis from the doctrine itself, taking into account the variety of approaches from legal scholars; who, through a detailed analysis of international legislation and state regulations, propose conceptualizations, characteristics, particularities, and effects of each of the legal institutions raised for the investigation, which in this case are a fundamental part of civil law. The evolution of societies has brought about new forms of family that are not necessarily traditional and consist of unions between a man and a woman to form a family. Nowadays, in various legislations around the world, the so-called equal marriage is recognized, which was achieved in Ecuador through a pronouncement by the Constitutional Court. There are also hundreds of homosexual couples who are in a de facto union and constantly fight for the recognition of their rights and their inclusion in the regulations. The importance of this research work lies in the study of two legal institutions that, although present in Ecuadorian legislation, deserve to be reviewed in accordance 5 with social evolution and their needs to protect society members with equity and full respect for their freedoms. The research methodology is qualitative, using the dogmatic and interpretative method of constitutional and legal norms, as through these methods, a response to the problem is offered based on the best possible reconstruction allowed by the legal material available. Additionally, since the social facts or phenomena studied in this work are measurable and quantifiable, I will measure and establish causal relationships between variables to explain the problem under study and the current social reality. Keywords: Marriage, Common-law Union, single-parent, nuclear family, rights, obligations, legal recognition.